A comparative analysis of collagen based dressings and polysaccharide microspheres for hemostasis management in hepatic stab wounds - Francisco José Sánchez del Valle; María Isabel Sánchez-Seco; Juan Garófano (Scientific Reports)
Abstract This study aims to evaluate two of the most commonly used products, the collagen-based patch (Hemopatch) and the micropolysaccharide microspheres powder (Perclot), in the context of stab liver injury in pigs. The objectives of this study were to assess blood loss at various time intervals up to 24 h, survival rates, and mean arterial pressure. The research involved 18 Large-White swine. The animals underwent a traumatic liver puncture through two 5 cm deep blade incisions that severed two main suprahepatic veins. Hemostatic surgical treatment was conducted for 12 min using two hemostatic agents. In the first 3 min after injury, the Hemopatch group lost less blood than the Perclot group, with 300 cc (222.5–415.0) compared to 555.0 cc (480.0–632.5) (p = 0.001). However, at 13–60 min post-injury, the Perclot group lost less blood than the Hemopatch group, 45.0 cc (32.5–135.0) compared to 305.0 cc (112.5–607.5) (p = 0.015). Lastly, the survival rate 24 h after injury was higher in the Perclot group (88.8%) compared to the Hemopatch group (44.4%) (p = 0.046). Several disparities were observed between Perclot and Hemopatch. Although Hemopatch demonstrates prompt bleeding reduction in the initial 3 min, Perclot is capable of stabilizing the clot and subsequently reducing long-term bleeding, ultimately increasing the likelihood of survival. These observations support the utilization of Perclot for managing severe hepatic hemorrhage.